Molecular wires – impact of π-conjugation and implementation of molecular bottlenecks. (15th October 2014) - Schubert, C.; Margraf, J. T.; Clark, T.; Guldi, D. M.
Abstract : We highlight recent progress in the field of electron transport through molecular bridges as integrative parts of electron donor–bridge–acceptor conjugates. Abstract : In this review we highlight recent progress in the field of photochemically and thermally induced electron transport through molecular bridges as integrative parts of electron donor–bridge–acceptor conjugates. The major emphasis is hereby on the design and the modular composition of the bridges. To this end, we will demonstrate that control over attenuation factors and reorganization energies, on one hand, as well as electronic and electron–vibration couplings, on the other hand, enables tuning electron transport over distances as short as 3.5 Å and as large as 50 Å by up to nine orders of magnitude. In terms of electron transport, the maximum extreme is given by carbon-bridged oligo- p -phenylenevinylenes of different lengths, while a zinc tetraphenylporphyrin free base tetraphenylporphyrin dyad constitutes the minimum extreme.